2018
DOI: 10.1111/jedm.12164
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Nonadditivity in Single‐Facet Generalizability Theory Applications: Tukey's Test

Abstract: Under the generalizability‐theory (G‐theory) framework, the estimation precision of variance components (VCs) is of significant importance in that they serve as the foundation of estimating reliability. Zhang and Lin advanced the discussion of nonadditivity in data from a theoretical perspective and showed the adverse effects of nonadditivity on the estimation precision of VCs in 2016. Contributing to this line of research, the current article directs the discussion of nonadditivity from a theoretical perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Tukey's test was utilized to evaluate scores for the scale and its subscales. The results of this test was not statistically significant, which means that the scale has the additivity feature (Lin & Zhang, 2018). The Hoteling T 2 test was used and the Response Bias of the scale was found to be T 2 = 70.40, p = .00.…”
Section: Discussionmentioning
confidence: 89%
“…Tukey's test was utilized to evaluate scores for the scale and its subscales. The results of this test was not statistically significant, which means that the scale has the additivity feature (Lin & Zhang, 2018). The Hoteling T 2 test was used and the Response Bias of the scale was found to be T 2 = 70.40, p = .00.…”
Section: Discussionmentioning
confidence: 89%
“…As such, although the variance components for the interaction effect observed in this study were evident, it is unclear how much random error contributed to the total score variance. This confounding nature, which is also discussed in Lin and Zhang’s (2018) study, is a limitation of current G theory designs. Second, the majority of the participants in the study were French and Arabic speakers whose reading proficiency levels ranged from low- to high-intermediate.…”
Section: Implications and Limitationsmentioning
confidence: 93%
“…They further found that person true score variance estimates were often underestimated when additive models were assumed. Lin and Zhang (2018) conducted simulation analyses to determine the Type-I and Type-II error rates for the one-degree of freedom test when applied to G-theory one-facet designs. They found that their test was generally well powered when detecting nonadditivity, and that it had an acceptable Type-I error rate when the data was additive.…”
Section: G-theory and Its Random-effects Anova Foundationmentioning
confidence: 99%